Buy-Side Analysts, Sell-Side Analysts, and Investment Decisions of Money Managers - Cheng, Yingmei; Liu, Mark H.; Qian, Jun (Journal of Financial and Quantitative Analysis, 2006)
Abstract We examine the role of financial analysts in forming institutional investors' investment decisions. In our model, a fund manager invests in a stock based on the optimal weighting of reports created by a biased sell-side analyst and an unbiased buy-side analyst. The manager puts a higher weight on the buy-side analyst's report when the quality of the buyside analyst's information relative to that of the sell-side analyst increases, or when the sell-side analyst's degree of bias or uncertainty about the bias increases. Utilizing a unique dataset of U.S. equity funds, we find evidence supporting our model predictions on how fund managers weigh buy-side research relative to sell-side and independent research.